A forma em performance: elementos para uma ressignificação dos gestos na regência - Marcos Antônio Silva Santos (2022)
Musical conducting, in a paradigmatic way, was consolidated by the end of the 19th century and the systematization of silent metric patterns were its backbone. This thesis proposes to analyse this paradigm - exemplified by four methods of conducting technique: Labuta (1995), Green (1987), Meier (2009) and Wittry (2014) - in comparison with contemporary conceptions and practices of musical form and performance. We seek to show how this model of conducting clashes with the practices of recognized conductors, represented here by Barenboim (2012), Sokhiev (2019) and Järvi (2016), as far as their gestures go far beyond the orthodox features advocated by the conducting textbooks. According to (1) topics of Adorno`s philosophy, especially the concepts of form and musical reproduction, (2) the conceptualizing perspectives of performance in Taylor (2012, 2013) and Zumthor (1993, 2002), and (3) the creative role of musical interpreters sustained by Cook (2013), Clarke (2005), Davidson (2011) and Leech-Wilkinson (2012) - all these key references operating in coordination - we will argue that what is been done in the performances of the conductors analyzed is the practice of a co-formalizing conducting. In other words, it is a "second moment" of handling the musical material (Adorno, 1989, 2008, 2014), in which the conductors, through their interpretive work, but mainly through their gestures, pair up with the composers in the task of recreating the formal dimension of music. In conclusion, as an effort to bring the teaching of conducting closer to this type of performance which deal with musical forms, occasionally presented by prominent names of the field, we try to propose gestural-formal interpretations based on five examples taken from J. Haydn, L. v. Beethoven, B. Bartok, R. Strauss and C. M. v. Weber.